1982
DOI: 10.1152/jappl.1982.52.2.434
|View full text |Cite
|
Sign up to set email alerts
|

Effect of muscle glycogen content on glucose uptake following exercise

Abstract: This study examined the effects of raising muscle glycogen by carbohydrate feeding and of keeping muscle glycogen low by carbohydrate restriction following exhausting exercise on the ability of perfused skeletal muscle to take up glucose and to synthesize glycogen. Muscle glycogen concentration was more than twice as high in the rats fed carbohydrate as in those not given carbohydrate. Muscle glycogen synthesis during a 30-min perfusion with glucose and insulin was significantly greater in the animals with low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
57
0
5

Year Published

1985
1985
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(68 citation statements)
references
References 0 publications
6
57
0
5
Order By: Relevance
“…14 CO 2 production from [U- 14 C]glucose mainly reflects CO 2 derived from the decarboxylation of glucose in the pentose phosphate pathway and in the pyruvate dehydrogenase step in the pathway of fatty acid synthesis. Because lipid synthesis was stimulated in these cells, we used [6][7][8][9][10][11][12][13][14] C]glucose to determine whether the overexpression of myophosphorylase also stimulated glucose oxidation. We found that there was no difference in the Glucose Uptake and Phosphorylation-The effect of phosphorylase dosage on the uptake and phosphorylation of the nonmetabolizable glucose analogue 2-deoxyglucose was studied (Table III).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 CO 2 production from [U- 14 C]glucose mainly reflects CO 2 derived from the decarboxylation of glucose in the pentose phosphate pathway and in the pyruvate dehydrogenase step in the pathway of fatty acid synthesis. Because lipid synthesis was stimulated in these cells, we used [6][7][8][9][10][11][12][13][14] C]glucose to determine whether the overexpression of myophosphorylase also stimulated glucose oxidation. We found that there was no difference in the Glucose Uptake and Phosphorylation-The effect of phosphorylase dosage on the uptake and phosphorylation of the nonmetabolizable glucose analogue 2-deoxyglucose was studied (Table III).…”
Section: Resultsmentioning
confidence: 99%
“…The system accounting for such effects appears to be located at a post-receptor level, because exercise does not affect the amount of insulin receptors or insulin-stimulated kinase activity (9,10). Breakdown of glycogen stores (11)(12)(13) or the activation of glycogen synthase (9) have been suggested as possible mediators of this phenomenon. On the other hand, even though these studies are consistent with the fact that glucose uptake is limited by glucose metabolism, other studies suggest that it is glucose transport that limits glucose uptake (14,15).…”
mentioning
confidence: 99%
“…Glucose-induced insulin resistance, also referred to as "glucose toxicity," has been studied in a number of experimental models. These include rats infused with high concentrations of glucose (4 -6), perfused rat hind limb muscles (7)(8)(9)(10), isolated muscles incubated in vitro (11,12), primary cultures of rat adipocytes (13)(14)(15), and muscles of transgenic mice overexpressing GLUT1 (16,17).…”
mentioning
confidence: 99%
“…One is that accumulation of large amounts of glycogen, as a result of glucose flooding into the cell, causes insulin resistance (7,11,18), possibly as a consequence of association of GLUT4-containing vesicles with glycogen particles (19,20). A second hypothesis is that glucose toxicity is mediated by activation of protein kinase C (5,21,22) resulting in increased serine and threonine phosphorylation of the insulin receptor, with a decrease in insulin stimulation of insulin receptor tyrosine kinase (21,(23)(24)(25).…”
mentioning
confidence: 99%
“…In the Gdepleted hearts, the lower preischemic glycogen is almost exhausted after the initial 10 min of LFI and this leads to a stimulation of GLUT4 translocation and glucose uptake. Similarly, exercise-induced stimulation of glucose uptake in skeletal muscles is greater when glycogen content is low and unable to supply endogenous substrate for glycolysis (6,14).…”
Section: Discussionmentioning
confidence: 99%